X分之40=3分之60 2.4:5=X:2分之7 4分之1.2=X分之0.6 1.75:0.35=1.2分之X 16分之5:4分之1=X:3.2 解比例
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 02:07:53
X分之40=3分之602.4:5=X:2分之74分之1.2=X分之0.61.75:0.35=1.2分之X16分之5:4分之1=X:3.2解比例X分之40=3分之602.4:5=X:2分之74分之1.2
X分之40=3分之60 2.4:5=X:2分之7 4分之1.2=X分之0.6 1.75:0.35=1.2分之X 16分之5:4分之1=X:3.2 解比例
X分之40=3分之60 2.4:5=X:2分之7 4分之1.2=X分之0.6 1.75:0.35=1.2分之X 16分之5:4分之1=X:3.2 解比例
X分之40=3分之60 2.4:5=X:2分之7 4分之1.2=X分之0.6 1.75:0.35=1.2分之X 16分之5:4分之1=X:3.2 解比例
X分之40=3分之60
x=40*3/60
x=2
2.4:5=X:2分之7
x=2.4*3.5/5
x=1.68
4分之1.2=X分之0.6
x=4*0.6/1.2
x=2
1.75:0.35=1.2分之X
x=0.35*1.2/1.75
x=0.24
16分之5:4分之1=X:3.2
x=5/16*3.2/0.25
x=4
X分之40=3分之60 2.4:5=X:2分之7 4分之1.2=X分之0.6 1.75:0.35=1.2分之X 16分之5:4分之1=X:3.2 解比例
X分之40=3分之60 2.4:5=X:2分之7 4分之1.2=X分之0.6 1.75:0.35=1.2分之X 16分之5:4分之1=X:3.2 解比例
2.4-2.5分之x-4=5分之3x
2.4-2分之x-4=5分之3x
解方程;3分之x+x-1分之6=x(x-1)分之x+5
4分之x+3=x-5分之x-1
4分之x+3=x-5分之x-1
x+3分之2x=60 x-5分之3x=120 解方程
5分之x+4-(x-5)=3分之x+3-2分之x-2
5分之(X+4)-(X-5)=3分之(X+3)-2分之(X-2)
2分之x-4分之3-4x=2-x-8分之5-3x
5分之x+4-(x-50)=3分之x+3-2分之x-2
2分之x+4-x+5=3分之x+3-6分之x-2
3分之1X +5分之1X + 6分之1X + 148 = X
(x+1)分之3x+2x分之(x+1)=2分之5
5分之x=5分之3:3分之5
x+5分之2=x分之1 x-4分之x-1=x-4分之3 2
求x(1)x:5分之6=4分之25 (2)6:x=5分之12 (3)x分之60=5分之2